Notau – the Hanseatic harbour at Avaldsnes, south-west Norway: written sources, maps and place-names (AmS-Skrifter, 2020)
Written sources, mostly of German origin from the fifteenth century, mention Notau, a Hanseatic harbour somewhere in the south-western part of Norway. Ships from towns, including Lübeck, Danzig and Kampen, called here. Dutch maps from the sixteenth and seventeenth centuries show that Notau was situated on the island of Karmøy in Rogaland county. The placename ‘Nottå’ has been used in modern times for locations at two islands belonging to the royal farm of Avaldsnes. Most probably one of these islands was called ‘Nautøy’ in the medieval period, becoming Notau in German. The written sources indicate that the Germans built houses in Notau, where the merchants are likely to have traded with the inhabitants of the  region.